Pengaruh Pemberian Pemberian Dark Chocolate terhadap Penurunan Tingkat Nyeri Dismenorhea Primer pada Mahasiswi Prodi Keperawatan Magelang - Utami, Pinilih Pangesti; Isworo, Adi; Hanafi, Moh (Jurusan Keperawatan FIKES UNSOED, 2017)
Primary dysmenorrhea is pain during menstruation without any pelvic abnormalities. Approximately 45-95% childbearing age women experience pain during menstruation. The incidence of primary dysmenorrhea in Indonesia is about 54.89%. The objective of this study is to determine the effect of dark chocolate on the decrease of pain level in primary dysmenorrhoea. This research used pre-experimental with one group pretest-posttest research design. This study involved 44 female nursing students. The data was collected using interview sheet and pain observation sheet. The bivariate data were analyzed using Wilcoxon test. The results showed that the mean of pain before provided 100 grams of dark chocolate was 5 (moderate pain) while the mean of pain after providing dark chocolate 100 gram was 2 (mild pain). The bivariate analysis of Wilcoxon's test obtained p 0,001 (